A Microfluidic Co‐Flow Route for Human Serum Albumin‐Drug–Nanoparticle Assembly. Issue 27 (28th April 2020) - Hakala, Tuuli A.; Davies, Sarah; Toprakcioglu, Zenon; Bernardim, Barbara; Bernardes, Gonçalo J. L.; Knowles, Tuomas P. J.
Abstract: Nanoparticles are widely studied as carrier vehicles in biological systems because their size readily allows access through cellular membranes. Moreover, they have the potential to carry cargo molecules and as such, these factors make them especially attractive for intravenous drug delivery purposes. Interest in protein‐based nanoparticles has recently gained attraction due to particle biocompatibility and lack of toxicity. However, the production of homogeneous protein nanoparticles with high encapsulation efficiencies, without the need for additional cross‐linking or further engineering of the molecule, remains challenging. Herein, we present a microfluidic 3D co‐flow device to generate human serum albumin/celastrol nanoparticles by co‐flowing an aqueous protein solution with celastrol in ethanol. This microscale co‐flow method resulted in the formation of nanoparticles with a homogeneous size distribution and an average size, which could be tuned from ≈100 nm to 1 μm by modulating the flow rates used. We show that the high stability of the particles stems from the covalent cross‐linking of the naturally present cysteine residues within the particles formed during the assembly step. By choosing optimal flow rates during synthesis an encapsulation efficiency of 75±24 % was achieved. Finally, we show that this approach achieves significantly enhanced solubility of celastrol in the aqueous phase and, crucially, reduced cellular toxicity. Abstract : Nanotechnology : We demonstrate a microfluidic co‐flow device to produce drug‐loaded albumin nanoparticles without additional cross‐linking steps. This method showed high loading efficiency of the lipophilic drug celastrol, which created spherical nanoparticles with considerable reduced drug cytotoxicity (see figure).